2021
DOI: 10.1159/000518279
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Inferior Meatal Antrostomy for Antrochoanal Polyps: A Long-Term Follow-Up

Abstract: <b><i>Background:</i></b> Endoscopic middle meatal antrostomy (EMMA) is considered the standard approach for surgical management of antrochoanal polyps (ACPs). Recently, an endoscopic inferior meatal antrostomy (EIMA) approach for clearing lesions in the maxillary sinus was described. In this study, we compared the long-term outcome of patients with ACP following surgical treatment using one of these 2 approaches (EIMA or EMMA). <b><i>Methods:</i></b> The medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…In addition, our and other studies found high IMA window closure rate for the patients with IMA [ 12 ]. Previous study suggested that the mucociliary clearance was toward all along the MS ostium even if IMA was performed [ 15 ], thus we believed that extended MMA via extended medial wall was enough but IMA wasn’t necessary for the treatment of FMS in most cases.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, our and other studies found high IMA window closure rate for the patients with IMA [ 12 ]. Previous study suggested that the mucociliary clearance was toward all along the MS ostium even if IMA was performed [ 15 ], thus we believed that extended MMA via extended medial wall was enough but IMA wasn’t necessary for the treatment of FMS in most cases.…”
Section: Discussionmentioning
confidence: 95%
“…The identification and removal of the origin are vital for preventing the ACP recurrence. Previous studies showed that most unilateral ACPs originated from the lateral wall and inferior regions [ 4 , 7 ]. Al-Balas et al [ 4 ] reported that 31.7% were located in the inferior wall, 12.2% in the anterior wall, 9.8% in the lateral wall, and 4.9% in the posterior wall.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study has shown that INA is superior to MMA as it does not void the Ostiomeatal Complex 16 .…”
Section: Discussionmentioning
confidence: 99%